Beach Morning-glory Ipomoea imperati and Railroad Vine Ipomoea pes-caprae subsp. brasiliensis - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Two species of Ipomoea are found in coastal beach plant communities of the Florida Panhandle; beach morning-glory (Ipomoea imperati) and railroad vine (Ipomoea pes-caprae subsp. brasiliensis). Beach morning-glory and railroad vine are distinguished by the colors of their corollas and the shapes of their leaves. Beach morning-glory flowers are white with yellow and purple in the throat and leaves are elliptical and notched; whereas railroad vine has a pink to purple flower and kidney-shaped leaves. Beach morning-glory flowers occur from spring to fall, while railroad vine flowers are present year-round. https://edis.ifas.ufl.edu/sg173